Application of Fermentation Technology in Animal Nutrition (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue on “Application of Fermentation Technology in Animal Nutrition” comprises 11 original research articles and 1 communication. Collectively, these contributions illustrate the promising future of fermentation technology in animal nutrition research, one that is committed to both tradition and innovation, with the objective of advancing the frontiers of fermentation science. Altogether, this Special Issue presents several original studies in the field of animal nutrition, including research on co-ensiling technology, silage additives, rumen fermentation, and related topics. These findings could help to improve feed resources, optimize silage quality and improve animal performance. As this Special Issue draws to a close, it is obvious that the field of silage research is not merely evolving, but undergoing a revolution. The challenges that lie ahead are considerable, but so are the opportunities. By addressing these challenges and pursuing the research directions outlined above, it is possible to ensure that fermentation technology will remain a critical aspect of animal nutrition, meeting the evolving needs of animal husbandry.